Gwiazdy złotej Pragi. (Gdynia : [s.n.], 1967)
Afisz inf. o występach.
Keywords: Korpolewski, Zbigniew -- (1934-2018).; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- życie artystyczne